2013
DOI: 10.14741/ijae/5.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Treatment on Surface Tension and Water Evaporation

Abstract: In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Moreover, it has also been found , that the intensity of the magnetic field has to be high to be able to cause a reduction in surface tension, which confirms the reliability of our surface tension results. In summary, a magnetic field has the ability to alter electric charges in favor of alterations in wettability toward being more water-wet without affecting the fluid chemistry of displacing fluids, hence increasing the sweep efficiency by enhancing the displacement of oil by water.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, it has also been found , that the intensity of the magnetic field has to be high to be able to cause a reduction in surface tension, which confirms the reliability of our surface tension results. In summary, a magnetic field has the ability to alter electric charges in favor of alterations in wettability toward being more water-wet without affecting the fluid chemistry of displacing fluids, hence increasing the sweep efficiency by enhancing the displacement of oil by water.…”
Section: Resultssupporting
confidence: 90%
“…Research showed that the HP treatment enhanced van der Waals interaction by reducing the C–C bond lengths, which led to molecular aggregation ( 34 , 35 ). The molecular aggregation reduced the surface tension of the liquid ( 36 , 37 ), thus enhancing the volatilization ( 38 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the above, it seemed worthwhile to conduct additional research on the impact of static magnetic fields on water's evaporation rate and surface tension. The impact of the MF depends on the time, the magnetic position, and magnetic density, as shown in Figure3, the relation between evaporation rate and MF [52].…”
Section: Magnetic Field Effect On Water Evaporation Ratementioning
confidence: 95%
“…Cai et al [51] observed that the magnetic field significantly decreases the surface tension of salty water. Besides, Amor et al [52] lowered the surface tension of saltwater by 24 percent by utilizing a magnetic field under hot climate settings. Likewise, Wang et al [53] observed that magnetic fields decrease surface tension and specific heat capacity.…”
Section: Magnetic Field Effect On Water Surface Tensionmentioning
confidence: 99%